Bagaimana Meningkatkan Kinerja Pemasaran Melalui Model Entrepreneurial Marketing Pada Ecopreneurship? - Nanda Andreas Octavini; Ayudia Dwi Puspitasari; Nopi Yana (JURNAL ILMIAH MANAJEMEN & BISNIS, 2023)
Purpose – The purpose of this study was to find out the role of womenpreneurship and the influence of ecopreneurship on the marketing performance of MSMEs through implementing the Entrepreneurial Marketing model.Methodology – The population are women who have eco-friendly SMEs in Sumatra. The sample was 50 womenpreneurs who own SMEs, which was obtained by purposive sampling. The criteria set by the researchers are: 1) women entrepreneurs who own MSMEs; 2) SMEs are eco-friendly. The data analysis is used SEM PLS.Findings – This study shows that ecopreneurship managed by women affects marketing performance only through Market Orientation and innovation. Entrepreneurial Orientation and value creation do not affect marketing performance.Originality/Novelty – Providing a new and valuable contribution to the understanding of how to improve marketing performance in Ecopreneurship using the Entrepreneurial Marketing Model, whose focus is different from conventional marketing and highlights sustainability as an essential element in marketing strategy.Implications – This study indicates that women-ecopreneurship must apply the suitable Entrepreneurial Marketing model to improve marketing performance.